1995
DOI: 10.1111/j.1469-7998.1995.tb02723.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology, life cycle and ecophysiology of the Antarctic miteAlaskozetes antarcticus

Abstract: The cryptostigmatid mite Alaskozetes antarcticus (Michael) is a dominant member of many terrestrial communities in the maritime Antarctic, where it survives extreme temperatures, short cold summers, numerous freeze-thaw cycles, desiccating conditions and a limited season for growth and reproduction. However, examination of features of its biology, from morphology, through life-history strategy to physiology, indicate very little specialization to the Antarctic environment. Alaskozetes antarcticus is a herbivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 42 publications
1
44
0
1
Order By: Relevance
“…In the absence of autoecological knowledge, such an increase might be used to suggest that Alaskozetes would be a predatory species, or at least forms part of a higher trophic level (Schneider et al 2004). However, existing literature gives no support to the proposal that Alaskozetes would be a predator species (Block 1985;Block and Convey 1995;Worland and Lukesova 2000). Alaskozetes can however, be abundant on and near animal carcasses (Goddard 1982), and feeding on such food sources and excreta may lead to a higher d 15 N signature.…”
Section: Food Choice Of Antarctic Soil Arthropodsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the absence of autoecological knowledge, such an increase might be used to suggest that Alaskozetes would be a predatory species, or at least forms part of a higher trophic level (Schneider et al 2004). However, existing literature gives no support to the proposal that Alaskozetes would be a predator species (Block 1985;Block and Convey 1995;Worland and Lukesova 2000). Alaskozetes can however, be abundant on and near animal carcasses (Goddard 1982), and feeding on such food sources and excreta may lead to a higher d 15 N signature.…”
Section: Food Choice Of Antarctic Soil Arthropodsmentioning
confidence: 95%
“…As there are no large herbivores, almost all this carbon is transferred to the soil (Davis 1981). It has previously been suggested that most of the carbon and nutrients will flow directly into the decomposition pathway without passing through a consumer level (Block 1985). However, the contribution of the dominant groups of soil arthropods, springtails and mites, within these nutrient flows is not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, quantitative ecological work was, until relatively recently, restricted largely to several maritime and sub-Antarctic Islands (see Block 1984;Lewis Smith 1984;Hänel & Chown 1999 for access to this literature), although early work had commenced, but has not been systematically continued, elsewhere (Janetschek 1967). In a similar vein, although more than 27 springtail and 60 mite species have been recorded from the Antarctic continent, comprehensive investigations of the autecology, life histories and environmental responses of these groups have, until recently, been restricted to just a few species, most notably the springtail Cryptopygus antarcticus and the mite Alaskozetes antarcticus (Block 1984;Block & Convey 1995;Convey 1996a).…”
Section: Introductionmentioning
confidence: 99%
“…La mayor proporción encontrada se explica por la asociación de estos arácnidos con los pingüinos que residen en esta zona protegida (Gressitt et al, 1963). Hasta el momento, Alaskozetes antarcticus intermedius es la especie reportada para el sitio y asociada a las colonias de pingüinos (Block & Convey, 1995). Estudios futuros buscarán determinar los ejemplares para confirmar si se trata de la especie mencionada anteriormente.…”
unclassified